Answer: 8359
Step-by-step explanation:
The formula for sample size needed for interval estimate of population proportion :-
![n=p(1-p)(\frac{z_{\alpha/2}}{E})^2](https://tex.z-dn.net/?f=n%3Dp%281-p%29%28%5Cfrac%7Bz_%7B%5Calpha%2F2%7D%7D%7BE%7D%29%5E2)
Given : The significance level : ![\alpha=1-0.95=0.05](https://tex.z-dn.net/?f=%5Calpha%3D1-0.95%3D0.05)
Critical value : ![z_{\alpha/2}}=z_{0.025}=\pm1.96](https://tex.z-dn.net/?f=z_%7B%5Calpha%2F2%7D%7D%3Dz_%7B0.025%7D%3D%5Cpm1.96)
Previous estimate of proportion : ![p=0.32](https://tex.z-dn.net/?f=p%3D0.32)
Margin of error : ![E=0.01](https://tex.z-dn.net/?f=E%3D0.01)
Now, the required sample size will be :-
![n=0.32(1-0.32)(\frac{1.96}{0.01})^2=8359.3216\approx8359](https://tex.z-dn.net/?f=n%3D0.32%281-0.32%29%28%5Cfrac%7B1.96%7D%7B0.01%7D%29%5E2%3D8359.3216%5Capprox8359)
Hence, the required sample size = 8359
What is the question you need help on
One inch of board is left
if you subtract the two 3 inches pieces from the board
the further subtract the 24 inches from the three 8 inches pieces you get 31-30
Well, I bet you want your answer right away! So here it is.
<span>Given <span>f (x) = 3x + 2</span> and <span>g(x) = 4 – 5x</span>, find <span>(f + g)(x), (f – g)(x), (f × g)(x)</span>, and <span>(f / g)(x)</span>.</span>
To find the answers, all I have to do is apply the operations (plus, minus, times, and divide) that they tell me to, in the order that they tell me to.
(f + g)(x) = f (x) + g(x)
= [3x + 2] + [4 – 5x]
= 3x + 2 + 4 – 5x
= 3x – 5x + 2 + 4
= –2x + 6
(f – g)(x) = f (x) – g(x)
= [3x + 2] – [4 – 5x]
= 3x + 2 – 4 + 5x
= 3x + 5x + 2 – 4
= 8x – 2
(f × g)(x) = [f (x)][g(x)]
= (3x + 2)(4 – 5x)
= 12x + 8 – 15x2 – 10x
= –15x2 + 2x + 8
<span>\left(\small{\dfrac{f}{g}}\right)(x) = \small{\dfrac{f(x)}{g(x)}}<span><span>(<span><span>g</span><span>f</span><span></span></span>)</span>(x)=<span><span><span>g(x)</span></span><span><span>f(x)</span></span><span></span></span></span></span><span>= \small{\dfrac{3x+2}{4-5x}}<span>=<span><span><span>4−5x</span></span><span><span>3x+2</span></span><span></span></span></span></span>
My answer is the neat listing of each of my results, clearly labelled as to which is which.
( f + g ) (x) = –2x + 6
( f – g ) (x) = 8x – 2
( f × g ) (x) = –15x2 + 2x + 8
<span>\mathbf{\color{purple}{ \left(\small{\dfrac{\mathit{f}}{\mathit{g}}}\right)(\mathit{x}) = \small{\dfrac{3\mathit{x} + 2}{4 - 5\mathit{x}}} }}<span><span>(<span><span>g</span><span>f</span><span></span></span>)</span>(x)=<span><span><span>4−5x</span></span><span><span>3x+2</span></span><span>
Hope I helped! :) If I did not help that's okay.
-Duolingo
</span></span></span></span>
B
they will be congruent if there is a pair of parallel lines